(untitled) (Applied Biological Research, 2018)
Mastitis is an infrequent condition in canines relative to the scenario of this disease in farm animals (Schlafer and Miller, 2007). Canine mastitis usually occurs in postpartum period but may also occur in later stages of pregnancy and pseudopregnancy (Wiebe and Howard, 2009). Usually mastitis is a disease of bacterial etiology (Orfanou et al., 2008), but parasitic etiology has also been reported (Park et al., 2007). The main bacterial agents involved are coliforms, Staphylococcus sp. and Streptococcus sp. (Wiebe and Howard, 2009). Affected animal usually displays general symptoms of fever, vomiting, dehydration, anorexia, trembling and decreased mothering behaviour. Canine mastitis has favourable prognosis when there is early diagnosis and appropriate treatment is provided. The laboratory diagnosis usually includes pH test, cytology and microbiology of milk. There are meagre reports wherein hematology and biochemistry assays have also been taken into consideration for mastitis diagnosis (Ververidis et al., 2007; Vasiu et al., 2016). This report describes a case of pseudopregnancy associated mastitis caused by Klebsiella pneumoniae (K. pneumoniae) in a Great Dane bitch and its successful therapeutic management.